A critical appraisal of the design, construction and influence of the Unité d’Habitation, Marseilles, France - Millais, Malcolm (Journal of Architecture and Urbanism, 2015)
The Unité d’Habitation is a seventeen-storey apartment block built between 1947 and 1952 in Marseilles, France. Today the construction of such a building, in almost any part of the world, would hardly be newsworthy; however the construction of the Unité d’Habitation not only attracted global interest at the time, but it can also be seen as one of the most influential buildings of the twentieth century. This was for a number of reasons. The architect was Charles-Edouard Jeanneret-Gris who, better known as Le Corbusier for most of his adult life, was probably the most influential architect of the twentieth century. The building, in many ways, initiated the hegemony of Modern Movement architecture throughout the world. But, perhaps most importantly, it was seen by much of the architectural profession as a prototype for how people should be housed in the future – with consequential major social, environmental and urban impacts. This paper examines the background of the design and describes the construction in detail. It also comments critically on the building’s suitability as a model for mass housing, revealing the extent of its various functional failings that have not, as far as the author is aware, previously been exposed.